The Lion King 2 [videorecording (DVD)] : Simba's pride - Rooney, Darrell; LaDuca, Rob (Walt Disney Studios Home Entertainment, 2017)
Kiara, Simba's daughter, meets Kovu, a young cub from Outlands and as their feelings for one another grow the rift between the Outlanders and Simba's pride deepens.